Studies on the non-European Endonura Cassagnau, 1979 (Collembola, Neanuridae, Neanurinae) ADRIAN SMOLIS (Poland), LOUIS DEHARVENG (France) & IGHOR J. KAPRUS (Ukraine) - Smolis, Adrian; Deharveng, Louis; Kaprus’, Ighor J. (Zootaxa, 2011)
Two new species of non-European Endonura, E. levantica sp. nov. (Israel) and E. asiatica sp. nov. (Kirgisia), are described and illustrated. E. reticulata (Axelson, 1905), the most widespread member of the genus, is redescribed on the basis of a new extensive material.